MODESTY AS A DOCTOR’S MORAL TRAIT OF CHARACTER - Stefurak, V. P.; Mykytyn, T. V.; Dovganych, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The paper deals with a mentor’s part in forming students’ personality, future professionals in the fields of medicine and biology. The main emphasis is given to their moral traits of character, namely to modest behavior as well as communication competence with future patients, such as a sincere, gentle word as a prerequisite for the behaviour of an educated and decent doctor.